Evaluation of Technical Incident Risk on the National Power Grid in the Context of Power Safety Growth: A Descriptive Study - Fîta, Daniel N.; Barb, Crina; Pasculescu, Dragos; Pana, Leon (Advanced Aspects of Engineering Research Vol. 14, 2021)
In the context of increasing the importance of power safety for national security, the security of power systems within the National Power Grid, must be an objective of major and constant interest for the national transmission and system operator. National Power Grid’s existence is to ensure that consumers' electrical or thermal energy needs are met in terms of protection, technicality, and cost. Evolutions in recent decades have shown the increase in vulnerabilities caused by: failure, destruction and/or disruption of technological infrastructures caused by acts of terrorism, natural disaster, negligence in service, work accidents of technical nature, technical incidents, criminal activities and lack of investment. For the critical analysis of the National Power Grid, 4 (four) possible risk scenarios with effects of instability of the power safety and with major effects on the national security were identified, described and evaluated: Risk Scenario 1 – Technical Incident, Risk Scenario 2 – Damage: Technical Incident Sequence, Risk Scenario 3 – Damage: Natural Disaster, Risk Scenario 4 – Damage: Terrorist Attack. The purpose of the paper is to describe and evaluate the Risk Scenario 1 – Technical Incident (which is most prevalent) on the power substations and to prevent potential disturbances in the safety of the power supply to consumer.